Step
*
2
1
1
1
1
1
1
of Lemma
imonomial-cons
.....assertion..... 
1. u : ℤ
2. v : ℤ List
3. ∀u,a:ℤ. ∀f:ℤ ⟶ ℤ.  (int_term_value(f;imonomial-term(<a, [u / v]>)) = int_term_value(f;imonomial-term(<a * (f u), v>)\000C) ∈ ℤ)
4. u@0 : ℤ
5. a : ℤ
6. f : ℤ ⟶ ℤ
7. int_term_value(f;imonomial-term(<a * (f u@0), [u / v]>)) = int_term_value(f;imonomial-term(<(a * (f u@0)) * (f u), v>\000C)) ∈ ℤ
8. v1 : ℤ List
9. [u / v] = v1 ∈ (ℤ List)
⊢ ∀t1,t2:int_term().
    ((int_term_value(f;t1) = int_term_value(f;t2) ∈ ℤ)
    
⇒ (int_term_value(f;accumulate (with value t and list item v):
                          t (*) vv
                         over list:
                           v1
                         with starting value:
                          t1))
       = int_term_value(f;accumulate (with value t and list item v):
                           t (*) vv
                          over list:
                            v1
                          with starting value:
                           t2))
       ∈ ℤ))
BY
{ ((Thin (-1) THEN ListInd (-1)) THEN Reduce 0) }
1
1. u : ℤ
2. v : ℤ List
3. ∀u,a:ℤ. ∀f:ℤ ⟶ ℤ.  (int_term_value(f;imonomial-term(<a, [u / v]>)) = int_term_value(f;imonomial-term(<a * (f u), v>)\000C) ∈ ℤ)
4. u@0 : ℤ
5. a : ℤ
6. f : ℤ ⟶ ℤ
7. int_term_value(f;imonomial-term(<a * (f u@0), [u / v]>)) = int_term_value(f;imonomial-term(<(a * (f u@0)) * (f u), v>\000C)) ∈ ℤ
⊢ ∀t1,t2:int_term().
    ((int_term_value(f;t1) = int_term_value(f;t2) ∈ ℤ) 
⇒ (int_term_value(f;t1) = int_term_value(f;t2) ∈ ℤ))
2
1. u : ℤ
2. v : ℤ List
3. ∀u,a:ℤ. ∀f:ℤ ⟶ ℤ.  (int_term_value(f;imonomial-term(<a, [u / v]>)) = int_term_value(f;imonomial-term(<a * (f u), v>)\000C) ∈ ℤ)
4. u@0 : ℤ
5. a : ℤ
6. f : ℤ ⟶ ℤ
7. int_term_value(f;imonomial-term(<a * (f u@0), [u / v]>)) = int_term_value(f;imonomial-term(<(a * (f u@0)) * (f u), v>\000C)) ∈ ℤ
8. u1 : ℤ
9. v1 : ℤ List
10. ∀t1,t2:int_term().
      ((int_term_value(f;t1) = int_term_value(f;t2) ∈ ℤ)
      
⇒ (int_term_value(f;accumulate (with value t and list item v):
                            t (*) vv
                           over list:
                             v1
                           with starting value:
                            t1))
         = int_term_value(f;accumulate (with value t and list item v):
                             t (*) vv
                            over list:
                              v1
                            with starting value:
                             t2))
         ∈ ℤ))
⊢ ∀t1,t2:int_term().
    ((int_term_value(f;t1) = int_term_value(f;t2) ∈ ℤ)
    
⇒ (int_term_value(f;accumulate (with value t and list item v):
                          t (*) vv
                         over list:
                           v1
                         with starting value:
                          t1 (*) vu1))
       = int_term_value(f;accumulate (with value t and list item v):
                           t (*) vv
                          over list:
                            v1
                          with starting value:
                           t2 (*) vu1))
       ∈ ℤ))
Latex:
Latex:
.....assertion..... 
1.  u  :  \mBbbZ{}
2.  v  :  \mBbbZ{}  List
3.  \mforall{}u,a:\mBbbZ{}.  \mforall{}f:\mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}.    (int\_term\_value(f;imonomial-term(<a,  [u  /  v]>))  =  int\_term\_value(f;imonomial-\000Cterm(<a  *  (f  u),  v>)))
4.  u@0  :  \mBbbZ{}
5.  a  :  \mBbbZ{}
6.  f  :  \mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}
7.  int\_term\_value(f;imonomial-term(<a  *  (f  u@0),  [u  /  v]>))  =  int\_term\_value(f;imonomial-term(<(a  *  \000C(f  u@0))  *  (f  u),  v>))
8.  v1  :  \mBbbZ{}  List
9.  [u  /  v]  =  v1
\mvdash{}  \mforall{}t1,t2:int\_term().
        ((int\_term\_value(f;t1)  =  int\_term\_value(f;t2))
        {}\mRightarrow{}  (int\_term\_value(f;accumulate  (with  value  t  and  list  item  v):
                                                    t  (*)  vv
                                                  over  list:
                                                      v1
                                                  with  starting  value:
                                                    t1))
              =  int\_term\_value(f;accumulate  (with  value  t  and  list  item  v):
                                                      t  (*)  vv
                                                    over  list:
                                                        v1
                                                    with  starting  value:
                                                      t2))))
By
Latex:
((Thin  (-1)  THEN  ListInd  (-1))  THEN  Reduce  0)
Home
Index